Efektivitas Bahan Ajar Bahasa dan Sastra Indonesia Berbasis HOTS (High Order Thinking Skill) Pada Materi Teks Laporan Hasil Observasi - Rika Kartika (Medan Resource Center, 2021)
This aim of the study determine the effectiveness of Indonesian Language and Literature Teaching Materials Based on HOTS (High Order Thinking Skill) in the text of the observation report. The method of this study is the experimental method with the design of the Two Pretest-Posttest Design Group which involves differences treatment between the two groups of experimental methods which give different treatments to the two classes, namely the experimental class and the control class. This experimental method also uses an experiment specifically designed to generate useful data to answer research questions. For the study data were taken from 67 samples from the population. The retrieval data is finished with an assignment instrument which is writing a Report Text of Observation Results based on field observations. The research hypothesis is the learning outcomes using HOTS-based teaching materials are more effective than module teaching materials. The data of this study were analyzed by the